Formulation and Efficacy Test of Antistress Aromatherapy Candles Containing Peppermint Leaf Essential Oil (Mentha Piperita L) and Clove Leaf Essential Oil (Syzygium Aromaticum L) on Mice (Mus Musculus) - Nazilla, Khunut; Rahmawati, Riana Putri; Sukoharjanti, Bintari Tri (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study aims to determine the effectiveness of aromatherapy candles containing peppermint (Mentha piperita L.) and clove (Syzygium aromaticum L.) essential oils at concentrations of 3%, 5%, and 7% on mice. Research Method: This study employed a laboratory experimental method with a post-test-only control group design. The formula used in this study was a combination of peppermint and clove with concentrations FII (2%:1%), FIII (3%:2%), and FIV (4%:3%), as well as negative and positive controls (lavender). The evaluation was conducted on physical tests of the candles, including organoleptic tests, burn time tests, and melting point tests. The antistress effectiveness testing was divided into five groups, each consisting of 5 mice. The first treatment involved the Tail Suspension Test to induce stress in the mice. Subsequently, the mice were exposed to aromatherapy candles, and the Forced Swimming Test was conducted. The test results were analyzed using the One-Way ANOVA test. Results and Discussion: All aromatherapy candle formulas met the physical evaluation test requirements. Formulas FII and FIII demonstrated antistress efficacy with a significance value of less than 0.05. Implications: These results indicate that the combination of peppermint leaf essential oil and clove leaf essential oil has potential as an active ingredient in anti-stress aromatherapy candles. Further research is needed to support its effectiveness on a broader scale.